IMPLEMENTASI KEBIJAKAN PENGELOLAAN DANA DESA DALAM MENINGKATKAN PERCEPATAN PEMBANGUNAN DI KABUPATEN KONAWE - Crisbiantoro, Jefry; Takwim, Takwim (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study provides an overview of the implementation of Village Fund management in Konawe District, as well as the factors that influence implementation and strategies that must be carried out in order to improve implementation, as well as providing assistance to Local Governments in developing Village Funds. The implementation of the Village Fund management policy in Konawe District has been carried out since 2015. However, with the approval of the goals, the implementation of the Village Fund in Konawe District has not been optimal. The planning formulation process has not yet been approved according to established procedures, discussion of the objectives of improving governance, development and community empowerment, has been carried out optimally, but the goal of continuing to increase the capacity of community institutions in the village in planning, implementing and developing development has not run optimally. Likewise, the accountability program has not been carried out optimally which does not have a standard operating procedure on the systematic arrangement of the responsibility. Some of the factors that influence the implementation of the Village Fund in the Konawe Regency are communication, resource capabilities, implementing attitudes, and bureaucratic structures. the main instrument in research is the researcher itself. Data sources used are primary data sources and secondary data relating to policies and empirical requirements for the implementation of the Village Fund Management Policy. In this study, also using survey research to obtain primary data on village funding policies in Konawe District.